Relationship between training supervision and evolution of the density of GPs: a 3-year cohort study on French cities between 2018 and 2021 - Anas Taha; Sébastien Dawidowicz; Véronique Orcel; Thibault Puszkarek; Marc Bayen; Sabine Bayen (BMC, 2022)
Abstract Context There is an uneven distribution of general practitioners (GPs) across territories of developed countries leading to inequalities in access to health care. Countries are implementing incentive or coercive policies depending on the characteristics of their health system. Several studies suggest that the location of practical training may influence the location of GPs' practices. The objective of this study is to investigate the existence of a relationship between training supervision and evolution of the density of GPs in French municipalities between 2018 and 2021. Methods The evolution of the density of GPs in almost all French municipalities between 2018 and 2021 was followed up. A bivariate statistical analysis was carried out to look for a relationship between the evolution of the density of GPs and the number of training supervisors. Other bivariate analyses were carried out with other factors likely to influence the density of GPs, such as the existence of financial aid in the territory or the age of GPs. A multivariate analysis with all the significant variables in bivariate analysis was then carried out using the stepwise descending method. Results A total of 34 990 (99.9%) French municipalities were included in the follow-up. Among these, 9427 (26.9%) had a GP and 3866 (11%) had a GP involved in the training supervision. The density of GPs in French cities decreased on average by 2.17% between 2018 and 2021. Territories without training supervisors decreased by 4.63% while those with at least one increased by 1.36% (p < 0.01). This significant relationship was also found in multivariate analysis. Conclusion The training supervision is associated with a better evolution of density of GPs in French municipalities. This association persisted when other factors were considered. The results of this 3-year follow-up may lead us to consider the training supervision as a factor to regulate the distribution of GPs.